RESIKO MANAJEMEN PROYEK - Joni, I Gede Putu (Jurnal Ilmiah Teknik Sipil; Vol. 16, No. 1 Januari 2012)
A project has a set of risks to achieve goals. For construction projects, the risk is an interesting thing, especially for the expansion started out as a national participation in a multi-national in a project. Problems frequent occurrence of natural disasters floods, as one of the risk analysis project management. Specifically limits the risk of a project is the variability of income as a result of variations in cash flow and output during umurinvestasi concerned. Risk management strategies are very important to establish at the beginning of the project and risk aimed at the entire project life cycle basis. Risk management includes several activities: estimating the risks, analyze risks, handle risks, learn from experience. Phase determination in all parts is to indicate the actual risk of the project. Participant management and overall project management should give priority to in order to handle risk and the approach that creates: a variety of ideas to find a solution to the most minimal impact, contract administration are balanced, the completion of the project risks early on, based on the content of the problem, using a technique ADR (Alternative Dispute Resolution )
Keywords: risk management, construction project